Lebanon Economic Monitor, Spring 2017 - World Bank (World Bank, Washington, DC, 2017)
The election of President Michel Aoun in October 2016 after almost two and a half years of a presidential vacancy, and the subsequent formation of a national unity government have generated hope for the resuscitation of the political process in Lebanon. Nonetheless, the protracted Syrian conflict is markedly worsening the country's vulnerabilities and remains an impediment to the return to potential growth. For the fifth year, Lebanon persists as the largest host (on a per capita basis) for displaced Syrians. In 2016, real GDP growth underwent a slight acceleration to reach an estimated 1.8 percent, compared to 1.3 percent in 2015. This was driven by an improvement in the real estate sector, marking a low threshold-effect from a weak performance in 2015 – cement deliveries expanded by 4.4 percent in 2016 compared to a contraction of 8.6 percent in 2015. Real GDP growth was also boosted by tourist arrivals, an indicator that registered an 11.2 percent growth in 2016. Nonetheless, economic activity persists below potential, inhibited by geopolitical and security conditions, which remain decidedly volatile.